Asuhan Keperawatan Keluarga dengan Masalah Gizi Kurang Keluarga Tn.S Terutama Pada An.R di Desa Trangsan Kecamatan Gatak Kabupaten Sukoharjo - Istriana, Murah; , Agustaria Budinugroho S. kep., Ns (2013)
Background: Malnutrition is a condition of very inadequate nutrition caused by low protein energy intake from daily meals and the condition occurs for long period of time. Method: The research is a descriptive one and sample is child R. Data is obtained by using interview, examination, activity observation and documentation and the research is performed collaboratively with a colleague. Result: After nursing care for 3 days, diagnoses emerged, namely, nutrition intake was less than needed and risk of developmental disturbance. Implementation was mostly agreeing with action plan. Conclusion: After nursing care for 3 days started from May 1st to 3rd 2013 for child R with malnutrition, researcher found real experience about administration of nursing care for the patient. Researcher can perform process familial nursing care directly ranged from examination, determination of diagnose, planning, implementation and evaluation, and documentation.